PENGARUH MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA PEGAWAI PADA BALAI PENDIDIKAN DAN PELATIHAN KEAGAMAAN BANJARMASIN - Mahfuzil Anwar (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, One of the important dimensions in understanding performance concept in motivation dimension, where performance is the function of motivation and skill. Some literature stated there are two motivation on individual self, intrinsic motivation and extrinsic motivation. Motivation formed from employee attitude in facing working situation in organization.The research method that used in this research is: 1) Based on the formulated research purpose, this research use level of explanation pattern, research that have purpose to explain posisition of factors that have been studied and correlation between one fctor to other factor. 2) Population and sample of the whole employee of Banjarmasin Religion Education and Training Bureau are 60 employees. 3) This research analysis uses double linear regression.The result of this research are: 1) the result of the test that have done to answer hypotesis I shows partially intrinsic motivation does not give significant effect to employee performance on Banjarmasin Religion Education and Training Bureau. 2) The test result shows there is significant effect on partial extrinsic motivation to employee on Banjarmasin Religion Education and Training Bureau. 3) The test result shows there is significant effect on simultaneous intrinsic motivation and extrinsic motivation on employye performance on Banjarmasin Religion Education and Training Bureau.